Introduced substrates trigger colonization by reef-associated fish in a degraded coastal system - Maryann S. Watson; Jon Dickson; Oscar Franken; Laura L. Govers; Tjisse van der Heide; Sterre Witte; Britas Klemens Eriksson (PLoS ONE, 2025)
Coastal reefs benefit the survival and growth of mobile organisms by providing shelter and increased food availability. Under increasing pressure from human activities, the coverage of subtidal reefs has decreased along the world’s coasts. This decline is motivating efforts to restore these important habitats by re-introducing hard substrates into the coastal zone. However, many such projects use artificial substrates, such as concrete or metal, that are not naturally occurring in the marine environment. We experimentally introduced hard substrates that were either historically common in a soft sediment-dominated ecosystem, or are mimicking these substrates with biodegradable material, and monitored the substrates for mobile species use (fish and invertebrates). Six substrates were tested: cockle shells, rocks of two sizes (cobbles and pebbles), wood, artificial reefs of calcium carbonate with shell fragments, and biodegradable structures based on potato starch. Within one year, fish and prawns were already attracted to all of the introduced substrates. On average, fish were nearly five times as abundant and prawn abundance increased nearly 30-fold on the artificial reefs, compared to the bare sand bottom control. The community composition on the reefs differed significantly from the sand bottom community, but there were no differences between the types of introduced substrates. Interestingly, the substrates attracted reef-associated fish, but also soft-sediment dependent species, such as different species of flatfish and gobies. Our results show that, even over shorter timespans, introductions of hard substrates provide opportunities to support associated mobile communities in degraded soft-sediment systems.